Receptor-targeted nanocarriers for therapeutic delivery to cancer - YU, BO (2010)
Efficient and site-specific delivery of therapeutic drugs is a critical challenge in clinical treatment of cancer. Nano-sized carriers such as liposomes, micelles, and polymeric nanoparticles have been investigated for improving bioavailability and pharmacokinetic properties of therapeutics via various mechanisms, for example, the enhanced permeability and retention (EPR) effect. Further improvement can potentially be achieved by conjugation of targeting ligands onto nanocarriers to achieve selective delivery to the tumour cell or the tumour vasculature. Indeed, receptor-targeted nanocarrier delivery has been shown to improve therapeutic responses both in vitro and in vivo. A variety of ligands have been investigated including folate, transferrin, antibodies, peptides and aptamers. Multiple functionalities can be incorporated into the design of nanoparticles, e.g., to enable imaging and triggered intracellular drug release. In this review, we mainly focus on recent advances on the development of targeted nanocarriers and will introduce novel concepts such as multi-targeting and multi-functional nanoparticles.